Consumer perception and readership pattern of toi readers – a case study (Trinity Journal of Management, IT & Media (TJMITM), 2018)
India is one of the fastest developing countries today. The  increased newspaper readership is the result of its growing  literacy and access to news on multiple technology and social  media platforms. The research is based on overall consumer  behaviour towards selection of newspaper with special  reference with, India's leading newspaper brand. Study of  consumer behaviour helps the organisations in improvisation of  various strategies by understanding customer psyche while  evaluating the various alternatives and selecting the best suited  one from all available. It also emphasises on factors influencing  buying decision and help the firm figure out the consumer's  needs and accordingly provide customised products as desired  by them.  The current study demonstrates how individuals make decision  regarding the preferences towards the selection of a leading  newspaper brand. Further, the research provided information  which is useful in taking various marketing decision and helped  to reduce the risk of consumer shift to various other brands  prevailing in the market. The study was conducted through a  survey of respondent's residing in NCR, Delhi. The research  concluded that promotional schemes offered by Times of India  had a positive correlation with the buying behaviour of the  subscribers. However there is a need to strengthen the  awareness of the promotional schemes on regular basis and  establishing a strong emotional connect with the readers.
Keywords: consumer behaviour; newspaper; emphasises